Liquid Fuel Evaporation under Supercritical Conditions (Communications in Computational Physics, 2020)
Molecular dynamics simulations are performed to study the supercriticalmixing process of the n-dodecane/nitrogen binary system. Previous studies haveshown the existence of supercritical phenomenon under certain conditions in modernpropulsion systems such as diesel engines. However, the physical mechanisms andinternal driving forces of this phenomenon are still not well understood. In this paper,we attempt to answer this question through simulating the diffusion and evaporationof gaseous nitrogen and liquid phase n-dodecane. It addresses under what conditionsthe supercritical transition phenomenon happens and what features the supercriticalevaporation process has. A unique configuration is constructed to mimic the evaporationof an n-dodecane thin film in an open nitrogen environment under conditionsranging from subcritical to supercritical. The detailed structure of the liquid-vapor interfaceduring the evaporating process is described and the evaporation rate and theinterface thickness are estimated, which show differences between subcritical and supercriticalevaporation. Results indicate that under relatively high pressure conditions,the liquid surface transitions into supercritical state, and the liquid-vapor interface expandssignificantly with vanishing surface tension, leading to a diffusion like mixingprocess. It is shown that the supercritical evaporation would happen under conditionsthat correspond to the in-cylinder conditions of a turbo-charged engine.